PENGELOLAAN PERPUSTAKAAN SEKOLAH - Median Efrina; Rambat Nur Sasongko; Zakaria Zakaria (UNIVERSITAS BENGKULU, 2017)
The purpose of research is to describe the management of school’s library in Public Junior High School 01 of Pondok Kubang Middle Bengkulu Regency. This research is qualitative descriptive. Subjects in this research are head of library and staffs. The techniques of data collection use observation, structured interview and documentation. The technique of data analysis uses qualitative descriptive method. The results of the research show that this school has done arranging daily work programmes, short term, middle term and long term. For implementing all that work programmes, so the principal establishs the organizational structure of the library managers as the implementers of daily activities as well job description of each part/work function in there. The principal doing evalution with purpose to know the achievement of work from various work programmes have been set that will be as inputs to make improvements of the library management in the next school years.